The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1007/s11420-015-9484-2
|View full text |Cite
|
Sign up to set email alerts
|

Handheld Navigation Device and Patient-Specific Cutting Guides Result in Similar Coronal Alignment for Primary Total Knee Arthroplasty: a Retrospective Matched Cohort Study

Abstract: Background: Proper alignment of total knee arthroplasty (TKA) is essential for TKA function and may reduce the risk of aseptic failure. Technologies that prevent malalignment may reduce the risk of revision surgery. Questions/Purposes: The purpose of this study was to compare two competing TKA systems that purport improved alignment: patient-specific instrumentation (PSI), and a handheld portable navigation device (NAV). Methods: After IRB approval, 49 consecutive PSI TKAs (40 patients) were matched based on p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 45 publications
1
10
0
Order By: Relevance
“…While custom cutting guides offer theoretical advantages, the majority of mid-to-long-term studies assessing their efficacy have demonstrated nonsuperiority [20][21][22][23][24][25][26] . Although the true value and cost-effectiveness of robotic technology have been debated, the use of robotic-arm assistance has demonstrated superiority to patient-specific instrumentation 27 and has shown the ability to improve TKA alignment in multiple studies 19,[28][29][30][31][32] . The findings of the current study, especially if alignment outlier status is linked to increases in implant failure in follow-up studies, may justify the increased use of these technologies in the future.…”
Section: Multivariate Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…While custom cutting guides offer theoretical advantages, the majority of mid-to-long-term studies assessing their efficacy have demonstrated nonsuperiority [20][21][22][23][24][25][26] . Although the true value and cost-effectiveness of robotic technology have been debated, the use of robotic-arm assistance has demonstrated superiority to patient-specific instrumentation 27 and has shown the ability to improve TKA alignment in multiple studies 19,[28][29][30][31][32] . The findings of the current study, especially if alignment outlier status is linked to increases in implant failure in follow-up studies, may justify the increased use of these technologies in the future.…”
Section: Multivariate Analysismentioning
confidence: 99%
“…As a result of the link between implant alignment outliers and early implant failure, efforts have been made to optimize alignment with the use of robotic navigation and patient-specific instrumentation [19][20][21][22][23][24][25][26][27][28][29][30][31][32] . However, little work has been conducted to identify the primary surgeon-specific factors that drive these outliers in order to understand the optimal patient populations in which to utilize this expensive technology.…”
mentioning
confidence: 99%
“…1). In addition, five studies 25,27,[37][38][39] were identified that compared ABN to CAS or PSI that formed part of a descriptive review.…”
Section: Resultsmentioning
confidence: 99%
“…After exclusion, two studies met final inclusion criteria. 27,37 Kawaguchi et al 27 retrospectively compared 34 ABN TKAs using KneeAlign2 for the distal femoral resection with 32 PSI TKAs (Biomet, Warsaw, IN, USA). They found significantly fewer outliers >3 in the HKA (9.1% versus 22.5%), CFA (0% versus 12.9%) and SFA (9% versus 37.5%) favouring ABN.…”
Section: Comparison Of Abn Versus Psimentioning
confidence: 99%
See 1 more Smart Citation